Gen Z and Uncertainty: Study of Management Accounting Decision-Making Behavior Based on Prospect Theory - Sudaryanti Dwiyani; Adib Noval; Sari Arista Fauzi Kartika; Fakriyyah Dewi Diah (SHS Web of Conferences, 2025)
The decision-making behavior of Generation Z as future decision makers is very important to know and understand. This study was motivated by the lack of research on the decision-making behavior of Generation Z, especially in the field of management accounting. Prospect Theory was chosen as the theoretical basis for testing the existence of decision-making bias, namely Certainty Effect, Reflection Effect and Isolation Effect. The instrument used was adopted from Kahneman & Tversky (1979) with adjustments according to Indonesian conditions. The results of the study showed support for Prospect Theory although not entirely. Students experienced a certainty effect but with a weaker effect compared to the results of the Kahneman & Tversky (1979) study. While in the Isolation effect and Reflection effect tests, students were significantly proven to experience it. The results of this study have an important impact on the design of accounting education in training students to make management accounting decisions in conditions full of uncertainty.